Experimental Electron Density Studies of Inorganic Materials. Issue 11 (15th May 2013) - Stokkebro Schmøkel, Mette; Overgaard, Jacob; Brummerstedt Iversen, Bo
Abstract The electron density of a molecular scale system is probably the most information‐rich observable in natural science, and experimental electron density determination based on X‐ray diffraction is a strong field of modern crystallography. Most studies concern small molecule organic or metal‐organic crystals, and indeed the experimental method and the subsequent data modeling and analysis have become a very versatile tool for such systems. However, inorganic materials in the form of high‐symmetry dense solids, often with extended structures and containing heavy atoms, represent one of the most serious challenges to the X‐ray electron density technique. For inorganic materials the scattering from the valence electrons is minute compared with the core electron scattering, and systematic errors such as extinction and absorption can be severe. In some sense studies of inorganic materials can be used as a benchmark for the current level of electron density analysis using X‐ray diffraction. Here we discuss the special challenges that face X‐ray electron density studies of inorganic materials. We discuss the special experimental requirements – basically the ideal X‐ray electron density experiment shines stable, intense, high energy, monochromatic X‐rays on minute single crystals at the lowest possible temperature, and the diffracted intensities are recorded on detectors with low background noise and large dynamic range. We also address the specific problems encountered when modeling very diffuse valence electrons in heavy atoms. Furthermore, for light atom materials topological analysis is often used as an analysis tool to extract information e.g. about chemical bonding, but for inorganic materials many of the commonly used descriptors are less informative, and other approaches are called for.